Polymer / nano-porous copper composite material and preparation method thereof
By preparing polymer/nanoporous copper composites, the brittleness problem of graded nanoporous copper materials is solved, and good toughness is achieved while maintaining a large specific surface area, and the composite performance is adjustable.
Patent Information
- Application Number
- CN202510114149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Due to its inherent brittleness, existing graded nanoporous copper materials are difficult to maintain a large specific surface area while having good toughness.
By preparing polymer/nanoporous copper composites, Mn-Cu alloys were prepared by smelting and heat treatment processes, followed by selective phase corrosion and electrochemical corrosion to form a porous structure, and a biphasic composite material was formed by impregnating the polymer material.
It is achieved to improve the toughness of nanoporous copper materials while maintaining an extremely high specific surface area, and the performance of composite materials can be adjusted by adjusting the ratio of polymer materials and nanoporous copper.
Smart Images

Figure CN119842184A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal materials, and in particular to a polymer / nano porous copper composite material and a preparation method thereof. Background Art
[0002] Nanoporous metals have extremely high application value in catalysis, driving, sensing, battery current collectors, etc. due to their extremely high surface area. Among them, graded nanoporous copper has attracted widespread attention due to its advantages such as simple preparation process and relatively low raw material prices.
[0003] However, there is an important problem with the existing graded nanoporous copper, which is its intrinsic brittleness. Since the pore-strut size in nanoporous metals is uniform, the fracture of any pore-strut in the structure will lead to stress concentration on the adjacent pore-strut during the load-bearing process. As long as this stress concentration exceeds the strength of the strongest pore-strut in the structure, it will cause catastrophic damage to the entire material. When tensile fracture, the elongation at fracture is often less than 1%; the existing methods of improving this brittleness by reducing the sample size or increasing the pore-strut size are not effective, and even if there is some improvement, it is at the expense of the extremely large surface area of nanoporous metals, and a large specific surface area is one of the most important and indispensable characteristics of nanoporous metals.
[0004] With the advancement of science and technology and the development of production technology, higher requirements have been placed on the mechanical stability of nanoporous copper. How to prepare nanoporous copper or nanoporous copper composite materials with good toughness and large surface area is an urgent problem to be solved. Therefore, it is necessary to continuously explore and research to find a simple preparation process that is easy to operate, produces stable and reliable samples, and obtains graded nanoporous copper or composite materials with good toughness, large specific surface area, and adjustable shape and size. Summary of the invention
[0005] In view of the problem of how the currently prepared nanoporous copper can have excellent toughness while maintaining a large surface area, the purpose of the present invention is to provide a method for preparing a polymer / nanoporous copper composite material. The preparation method of the polymer / nanoporous copper composite material prepared by the present invention is simple and convenient, with relatively low cost, and the size and shape of the finished product can be adjusted, the toughness is good, and the specific surface area is large, which is of great significance to the preparation, theoretical research and application of nanoporous metals.
[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0007] A method for preparing a polymer / nano porous copper composite material, the method comprising the following steps:
[0008] (1) preparing a certain proportion of pure copper and pure manganese, and smelting to prepare a Mn-Cu binary alloy;
[0009] (2) performing homogenization annealing treatment on the smelted Mn-Cu alloy to obtain a γ single-phase alloy, and then rolling;
[0010] (3) Recrystallization annealing of the γ single-phase alloy;
[0011] (4) subjecting the γ single-phase alloy after recrystallization annealing to aging treatment to precipitate the α phase to obtain an α / γ dual-phase alloy;
[0012] (5) placing the Mn-Cu alloy with α / γ dual-phase structure in a weakly acidic aqueous solution of sufficient content of acetic acid, ascorbic acid, ammonium sulfate, ammonium chloride, etc., for selective phase corrosion, wherein the α phase is completely corroded to form macropores, and the γ phase is retained to form porous γ-Mn(Cu);
[0013] (6) Using an impregnation method, a uniform mixture of a certain proportion of polymer and a curing agent is introduced into the porous γ-Mn(Cu). After the polymer material is cured, a polymer / γ-Mn(Cu) dual-phase composite material is formed.
[0014] (7) The prepared polymer material / γ-Mn (Cu) dual-phase composite material is placed in an acidic aqueous solution of sufficient content of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, etc., and electrochemical corrosion or free chemical corrosion without potential application is carried out. The Mn element in the γ-Mn (Cu) phase is corroded to a content of less than 2at.%, thereby forming nano-scale pores.
[0015] In the above step (1), the Mn content in the precursor Mn-Cu alloy is 70%-90% (atomic ratio).
[0016] In the above step (2), the annealing temperature ranges from 700 to 900°C.
[0017] In the above step (3), the annealing temperature is 700-900°C.
[0018] In the above step (4), the aging temperature ranges from 500 to 750°C.
[0019] In the above step (5), the selective phase corrosion temperature is 10-50°C
[0020] In the above step (6), the polymer material is in liquid state during dipping and becomes solid state after curing. The curing time varies slightly depending on the type of polymer material. The dipping temperature is 10-50°C.
[0021] In the above step (7), the dealloying temperature is 0-80°C.
[0022] The polymer / nanoporous copper composite material prepared by the above method has good toughness and extremely high specific surface area. The composite material can achieve a wide range of adjustments in the ratio of nanoporous copper to polymer materials while maintaining a large surface area and excellent toughness.
[0023] The design mechanism of the present invention is as follows:
[0024] 1. By changing the ratio of pure copper to pure manganese in step (1), the ratio of the polymer phase to the nanoporous copper phase in the composite material can be changed.
[0025] 2. After the aging treatment in step (3), as shown in the attached Figure 1 As shown in the figure, in the Mn-Cu alloy with α / γ dual-phase structure, the α-phase Mn content is >98at.%, which can be completely corroded in an acidic aqueous solution to form macropores with a pore diameter equivalent to the α-phase particle size. When the Mn content in the γ phase is 40-70at.%, the Mn in it cannot be or can only be dealloyed and corroded in a small amount in a weakly acidic aqueous solution. Therefore, porous γ-Mn(Cu) can be obtained by free corrosion or electrochemical corrosion of the Mn-Cu alloy with α / γ dual-phase structure.
[0026] 3. By changing the type of polymer material in step (6), the properties of the composite material can be changed.
[0027] 4. By changing the aging treatment temperature and time in steps (3) and (4), the content and size of the α phase in the alloy, i.e., the size and proportion of the polymer phase in the porous γ-Mn(Cu), i.e., the final polymer / nanoporous copper composite material, can be regulated. By changing the dealloying corrosion temperature in step (6), the pore size of the pores in the nanoporous copper phase can be regulated.
[0028] 5. Since the last step of the preparation is dealloying to form nanopores, it can be ensured that the sample has a very large specific surface area.
[0029] The advantages and beneficial effects of the present invention are as follows:
[0030] (1) Low preparation cost. Compared with the previous powder sintering method, the cost of preparing precursor alloy by smelting + heat treatment is lower.
[0031] (2) Large sample size: Smelting can produce large samples.
[0032] (3) The properties of composite materials can be controlled. By changing the type of polymer material in the composite material, the mechanical and other properties of the composite material can be changed to a large extent, such as Figure 5 As shown, when the composite material is impregnated with a flexible polymer material, excellent deformability can be obtained. When the composite material is impregnated with polytetrafluoroethylene (PTFE), excellent lubricity and hydrophobicity can be obtained.
[0033] (4) The ratio of polymer materials and nanoporous copper in the composite material can be controlled. By changing the composition of the master alloy and the temperature and time of the aging treatment, the content and size of the α phase in the alloy, that is, the ratio and size of the polymer materials in the final composite material, can be controlled. By changing the dealloying corrosion temperature, the pore size of the nanoporous copper phase can be controlled. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 Cu-Mn equilibrium phase diagram, in the diagram (Cu,γ-Mn) is the γ phase, and α(Mn) is the α phase.
[0035] Figure 2 These are the physical pictures and corresponding XRD spectra of each stage in the preparation process of the polymer / nanoporous copper composite material in Example 2: (a) physical pictures of each stage in the preparation process of the polymer / nanoporous copper composite material, (b) XRD spectra of each stage in the preparation process of the polymer / nanoporous copper composite material.
[0036] Figure 3 The scanning electron microscope images of the polymer / nanoporous copper composite materials prepared in Examples 1, 2 and 3 are as follows: (a) Case 1 (Example 1), (b) Case 2 (Example 2), (c) Case 3 (Example 3), (d) Case 2 (Example 2) high magnification.
[0037] Figure 4 Scanning electron microscope images of hierarchical nanoporous copper prepared in comparative example: (a) low magnification, (b) high magnification.
[0038] Figure 5 The uniaxial tensile engineering stress-strain curves of the polymer / nanoporous copper composite materials prepared in Examples 1, 2, and 3.
[0039] Figure 6 The engineering stress-strain curve of the hierarchical nanoporous copper prepared in comparative example under uniaxial tension.
[0040] Figure 7 The electrochemical driving performance of the composite material in Example 3 and the hierarchical nanoporous copper in the comparative case is compared. DETAILED DESCRIPTION
[0041] The present invention provides a method for preparing a polymer / nano porous copper composite material. The present invention is further illustrated by a plurality of specific implementation cases and comparative cases below.
[0042] Embodiment 1:
[0043] (1) Prepare pure copper and pure manganese (mass purity requirement ≥ 99.9%) according to the atomic ratio of Mn:Cu = 90:10 (at.%), and prepare Mn by electric arc furnace smelting.90 Cu 10 (at.%) alloy button-shaped ingot, the ingot diameter is about 10mm and the height is about 6mm.
[0044] (2) The as-cast Mn-Cu alloy button ingot is subjected to homogenization heat treatment and then cooled to room temperature to obtain a γ single-phase alloy. The heat treatment temperature is 850°C, the heat treatment time is 24 hours, and the cooling method is water cooling.
[0045] (3) The samples after the above homogenization heat treatment were subjected to room temperature cold rolling treatment, with a total rolling pass of 10 times and a total rolling reduction of 80%. The final plate size was about 18 mm × 5 mm × 1 mm (length × width × thickness).
[0046] (4) The rolled Mn-Cu alloy was recrystallized and annealed and then cooled to room temperature. The heat treatment temperature was 750°C, the heat treatment time was 30 min, and the cooling method was water cooling. Scanning electron microscopy showed that an equiaxed Mn-Cu alloy was finally obtained.
[0047] (5) The obtained equiaxed Mn-Cu alloy was subjected to aging heat treatment and then cooled to room temperature to obtain an α / γ dual-phase alloy. The aging treatment temperature was 650°C, the heat treatment time was 5h, and the cooling method was water cooling. Combined with SEM observation and EDS analysis, it can be seen that the chemical composition of the α phase is Mn 99 Cu1 (at.%), volume proportion ~78%, γ phase chemical composition is Mn 54 Cu 46 (at.%), accounting for ~22% by volume.
[0048] (6) The Mn-Cu alloy after aging heat treatment was placed in 1L of 0.1mol / L ascorbic acid aqueous solution for selective phase corrosion (corrosion of α phase) at a temperature of 25°C. After 24h of corrosion, no obvious bubbles escaped, and the phase corrosion was completed, thus obtaining micron porous γ-Mn(Cu) with an average pore size of 4.8μm, a pore size distribution range of 0.5-10μm, and a porosity of 0.78.
[0049] (7) The microporous γ-Mn (Cu) obtained after phase corrosion is placed in a vacuum impregnation device (manufacturer: Shenyang Kejing Automation Equipment Co., Ltd., model: CXQ-2500), with a vacuum degree of 100 Pa. 0.1L of epoxy resin and its curing agent (manufacturer: Easy Composites Asia Ltd, model: EF80) are prepared according to a mass ratio of 2:1, and mixed evenly to obtain an epoxy resin impregnation liquid. The microporous γ-Mn (Cu) is placed in the epoxy resin impregnation liquid to impregnate the microporous γ-Mn (Cu) with a flexible epoxy resin. After impregnation at room temperature for 2 hours, the epoxy resin / γ-Mn (Cu) dual-phase composite material is obtained after curing at room temperature for 24 hours.
[0050] (8) The vacuum impregnated polymer material / γ-Mn (Cu) dual-phase composite material (as the working electrode) was placed in a three-electrode system of 500 mL of 0.01 mol / L + 1 mol / L KCl aqueous solution for constant potential electrochemical dealloying at a temperature of 25°C, a dealloying voltage of -0.30 V, a reference electrode of Ag / AgCl electrode, a counter electrode of Ag wire, and an initial current of about 10 mA. After 12 h of dealloying, when the current was less than 10 μA, the dealloying corrosion was completed, and an epoxy resin / nanoporous copper composite material was obtained, and the Mn element content in the metal phase was 0.5 at.%, as shown in the scanning electron microscope image. Figure 3 a, wherein the volume proportion of epoxy resin is V=0.78, the average width of epoxy resin phase is W=4.8 μm, the overall porosity is P=0.12, the nanopore size in the nanoporous copper phase is D=42 nm, and the pore size distribution range is 20-100 nm.
[0051] (9) The obtained epoxy resin / nanoporous copper composite material was subjected to uniaxial tensile mechanical property test (sample gauge section size: 5 mm × 2 mm × 1 mm (length × width × thickness), strain rate: 1 × 10 -4 s -1 , testing equipment: Instron 5982), stress-strain curves are shown in Figure 5 As shown, it can be seen that it has excellent toughness.
[0052] Embodiment 2:
[0053] (1) Prepare pure copper and pure manganese (mass purity requirement ≥ 99.9%) according to the atomic ratio of Mn:Cu = 85:15 (at.%), and prepare Mn by electric arc furnace smelting. 85 Cu 15 (at.%) alloy button-shaped ingot, the ingot diameter is about 10mm and the height is about 6mm.
[0054] (2) The as-cast Mn-Cu alloy button ingot was subjected to homogenization heat treatment and then cooled to room temperature to obtain a γ single-phase alloy. The heat treatment temperature was 850°C, the heat treatment time was 24 h, and the cooling method was water cooling. The XRD characterization results are shown in FIG. Figure 2 b.
[0055] (3) The samples after the homogenization heat treatment were subjected to room temperature cold rolling. The total number of rolling passes was 10 and the total rolling reduction was 80%. The final plate size was about 18 mm × 5 mm × 1 mm (length × width × thickness). The actual photo is shown in Figure 2 As shown in a.
[0056] (4) The rolled Mn-Cu alloy was recrystallized and annealed and then cooled to room temperature. The heat treatment temperature was 750°C, the heat treatment time was 30 min, and the cooling method was water cooling. Scanning electron microscopy showed that an equiaxed Mn-Cu alloy was finally obtained.
[0057] (5) The obtained equiaxed Mn-Cu alloy is subjected to aging heat treatment and then cooled to room temperature to obtain an α / γ dual-phase alloy. The aging treatment temperature is 650°C, the heat treatment time is 5 hours, and the cooling method is water cooling. Figure 2 As shown in a. Combining SEM observation and EDS analysis, it can be seen that the chemical composition of the α phase is Mn 99 Cu1 (at.%), volume proportion ~67%, γ phase chemical composition is Mn 53 Cu 47 (at.%), accounting for ~33% by volume.
[0058] (6) The Mn-Cu alloy after aging heat treatment was placed in 1L of 0.1mol / L ascorbic acid aqueous solution for selective phase corrosion (corrosion of α phase) at a temperature of 25°C. After 24h of corrosion, no obvious bubbles escaped, and the phase corrosion was completed, and micron porous γ-Mn (Cu) was obtained, with an average pore size of 3.1μm, a pore size distribution range of 0.5-10μm, and a porosity of 0.67. The actual photo is shown in the figure. Figure 2 The XRD characterization results are shown in a. Figure 2 b.
[0059] (7) The microporous γ-Mn (Cu) obtained after phase corrosion is placed in a vacuum impregnation device (manufacturer: Shenyang Kejing Automation Equipment Co., Ltd., model: CXQ-2500) with a vacuum degree of ~100 Pa. 0.1L of epoxy resin and its curing agent (manufacturer: Easy Composites Asia Ltd, model: EF80) are prepared in a mass ratio of 2:1 and mixed evenly to obtain an epoxy resin impregnation solution. The microporous γ-Mn (Cu) is placed in the epoxy resin impregnation solution to impregnate the microporous γ-Mn (Cu) with a flexible epoxy resin. After immersion at room temperature for 2 hours, the epoxy resin / γ-Mn (Cu) dual-phase composite material is obtained after curing at room temperature for 24 hours. The actual picture is as follows Figure 2 The XRD characterization results are shown in a. Figure 2 b.
[0060] (8) The vacuum impregnated polymer material / γ-Mn (Cu) dual-phase composite material (as the working electrode) was placed in a three-electrode system of 500 mL of 0.01 mol / L + 1 mol / L KCl aqueous solution for constant potential electrochemical dealloying at a temperature of 25°C, a dealloying voltage of -0.30 V, a reference electrode of Ag / AgCl electrode, a counter electrode of Ag wire, and an initial current of about 10 mA. After 12 h of dealloying, when the current was less than 10 μA, the dealloying corrosion was completed, and an epoxy resin / nanoporous copper composite material was obtained, and the Mn element content in the metal phase was 0.5 at.%, as shown in the scanning electron microscope image. Figure 3 b, wherein the volume proportion of epoxy resin is V=0.67, the average width of epoxy resin phase is W=3.1 μm, the overall porosity is P=0.18, the nanopore size in the nanoporous copper phase is D=43 nm, and the pore size distribution range is 20-100 nm.
[0061] (9) The obtained epoxy resin / nanoporous copper composite material was subjected to uniaxial tensile mechanical property test (sample gauge section size: 5 mm × 2 mm × 1 mm (length × width × thickness), strain rate: 1 × 10 -4 s -1 , testing equipment: Instron 5982), stress-strain curves are shown in Figure 5 As shown, it can be seen that it has excellent toughness.
[0062] Embodiment 3:
[0063] (1) Prepare pure copper and pure manganese (mass purity requirement ≥ 99.9%) according to the atomic ratio of Mn:Cu = 80:20 (at.%), and prepare Mn by electric arc furnace smelting. 80 Cu 20 (at.%) alloy button-shaped ingot, the ingot diameter is about 10mm and the height is about 6mm.
[0064] (2) The as-cast Mn-Cu alloy button ingot is subjected to homogenization heat treatment and then cooled to room temperature to obtain a γ single-phase alloy. The heat treatment temperature is 850°C, the heat treatment time is 24 hours, and the cooling method is water cooling.
[0065] (3) The samples after the above homogenization heat treatment were subjected to room temperature cold rolling treatment, with a total rolling pass of 10 times and a total rolling reduction of 80%. The final plate size was about 18 mm × 5 mm × 1 mm (length × width × thickness).
[0066] (4) The rolled Mn-Cu alloy is recrystallized and annealed and then cooled to room temperature. The heat treatment temperature is 720°C, the heat treatment time is 30 min, and the cooling method is water cooling. Scanning electron microscopy observation shows that an equiaxed Mn-Cu alloy is finally obtained.
[0067] (5) The obtained equiaxed Mn-Cu alloy was subjected to aging heat treatment and then cooled to room temperature to obtain an α / γ dual-phase alloy. The aging treatment temperature was 650°C, the heat treatment time was 5h, and the cooling method was water cooling. Combined with SEM observation and EDS analysis, it can be seen that the chemical composition of the α phase is Mn 99 Cu1 (at.%), volume percentage ~59%, γ phase chemical composition is Mn 51 Cu 49 (at.%), accounting for ~41% by volume.
[0068] (6) The Mn-Cu alloy after aging heat treatment was placed in 1L of 0.1mol / L ascorbic acid aqueous solution for selective phase corrosion (corrosion of α phase) at a temperature of 25°C. After 24h of corrosion, no obvious bubbles escaped, and the phase corrosion was completed, thus obtaining micron porous γ-Mn(Cu) with an average pore size of 2.1μm, a pore size distribution range of 0.5-10μm, and a porosity of 0.59.
[0069] (7) The microporous γ-Mn (Cu) obtained after phase corrosion is placed in a vacuum impregnation device (manufacturer: Shenyang Kejing Automation Equipment Co., Ltd., model: CXQ-2500), with a vacuum degree of 100 Pa. 0.1L of epoxy resin and its curing agent (manufacturer: Easy Composites Asia Ltd, model: EF80) are prepared according to a mass ratio of 2:1, and mixed evenly to obtain an epoxy resin impregnation liquid. The microporous γ-Mn (Cu) is placed in the epoxy resin impregnation liquid to impregnate the microporous γ-Mn (Cu) with a flexible epoxy resin. After impregnation at room temperature for 2 hours, the epoxy resin / γ-Mn (Cu) dual-phase composite material is obtained after curing at room temperature for 24 hours.
[0070] (8) The vacuum impregnated polymer material / γ-Mn (Cu) dual-phase composite material (as the working electrode) was placed in a three-electrode system of 500 mL of 0.01 mol / L + 1 mol / L KCl aqueous solution for constant potential electrochemical dealloying at a temperature of 25°C, a dealloying voltage of -0.30 V, a reference electrode of Ag / AgCl electrode, a counter electrode of Ag wire, and an initial current of about 10 mA. After 12 h of dealloying, when the current was less than 10 μA, the dealloying corrosion was completed, and an epoxy resin / nanoporous copper composite material was obtained. The Mn element content in the metal phase was 0.5 at.%, and the scanning electron microscope image was as follows: Figure 3 c, wherein the volume proportion of epoxy resin is V=0.59, the average width of epoxy resin phase is W=2.1 μm, the overall porosity is P=0.21, the nanopore size in the nanoporous copper phase is D=42 nm, and the pore size distribution range is 20-100 nm.
[0071] (9) The obtained epoxy resin / nanoporous copper composite material was subjected to uniaxial tensile mechanical property test (sample gauge section size: 5 mm × 2 mm × 1 mm (length × width × thickness), strain rate: 1 × 10 -4 s -1 , testing equipment: Instron 5982), stress-strain curves are shown in Figure 5 As shown, it can be seen that it has excellent toughness.
[0072] Comparative Example:
[0073] (1) Prepare pure copper and pure manganese (mass purity requirement ≥ 99.9%) according to the atomic ratio of Mn:Cu = 80:20 (at.%), and prepare Mn by electric arc furnace smelting. 80 Cu 20 (at.%) alloy button-shaped ingot, the ingot diameter is about 10mm and the height is about 6mm.
[0074] (2) The as-cast Mn-Cu alloy button ingot is subjected to homogenization heat treatment and then cooled to room temperature to obtain a γ single-phase alloy. The heat treatment temperature is 850°C, the heat treatment time is 24 hours, and the cooling method is water cooling.
[0075] (3) The samples after the above homogenization heat treatment were subjected to room temperature cold rolling treatment, with a total rolling pass of 10 times and a total rolling reduction of 80%. The final plate size was about 18 mm × 5 mm × 1 mm (length × width × thickness).
[0076] (4) The rolled Mn-Cu alloy is recrystallized and annealed and then cooled to room temperature. The heat treatment temperature is 720°C, the heat treatment time is 30 min, and the cooling method is water cooling. Scanning electron microscopy observation shows that an equiaxed Mn-Cu alloy is finally obtained.
[0077] (5) The obtained equiaxed Mn-Cu alloy was subjected to aging heat treatment and then cooled to room temperature to obtain an α / γ dual-phase alloy. The aging treatment temperature was 650°C, the heat treatment time was 5h, and the cooling method was water cooling. Combined with SEM observation and EDS analysis, it can be seen that the chemical composition of the α phase is Mn 99 Cu1 (at.%), volume percentage ~59%, γ phase chemical composition is Mn 51 Cu 49 (at.%), accounting for ~41% by volume.
[0078] (6) The aging treated Mn-Cu alloy was placed in a 1L 0.1mol / L HCl aqueous solution and free-corroded for dealloying at a temperature of 40°C. After 12h of corrosion, no obvious bubbles escaped, and the dealloying was completed, and a graded nanoporous copper was obtained, such as Figure 4 As shown, the volume proportion of macropores is V=0.59, the pore size of macropores is L(W)=2.1 μm, the pore size distribution range is 0.5-10 μm, the pore size of small pores is D=45 nm, the pore size range is 20-100 nm, and the overall porosity is P=0.80.
[0079] (7) The obtained graded nanoporous copper was subjected to uniaxial tensile mechanical property test (sample gauge section size: 5 mm × 2 mm × 1 mm (length × width × thickness), strain rate: 1 × 10 -4 s -1 , test equipment: Instron5982), such as Figure 6 As shown, it is extremely brittle and breaks when the tensile strain is 0.3%.
[0080] The porous structure parameters and tensile mechanical properties of all the above cases are summarized in Table 1. By comparing Examples 1, 2, and 3, it can be seen that the proportion of polymer materials in the final composite material sample can be regulated by adjusting the precursor alloy composition, thereby affecting its mechanical properties. By comparing Examples 1, 2, and 3 with the comparative case, it can be seen that the final composite material sample has a larger tensile elongation at break than pure nanoporous copper, that is, it exhibits better toughness.
[0081] Table 1 Summary of porous structure parameters and tensile mechanical properties in the case
[0082]
[0083] Due to its extremely high specific surface area and through-pore structure, nanoporous metals have extremely high application value in the fields of lithium batteries, electrocatalytic hydrogen production, and driving. The polymer nanoporous copper composite material prepared by the present invention is based on graded nanoporous copper, and the macropores are filled with polymers to improve its tensile plasticity and toughness. At the same time, the small pores can still maintain the open-pore structure, and the specific surface area of the structure remains basically unchanged, which has no effect on the application of nanoporous metals in the fields of electrocatalytic hydrogen production and driving. Referring to the experimental scheme of Q. Bai, et al. Electrochemistry Communications 124 (2021) 106940, the present invention conducts electrochemical driving experiments on the composite material in Example 3 and the graded nanoporous copper in the comparative example. The driving sample size is 1×2×2mm 3 (as the working electrode), the drive was carried out in the three-electrode system of AUTOLAB PASTAT (the reference electrode was Ag / AgCl electrode, and the counter electrode was Ag wire), the electrolyte was 200mL of 1mol / LNaOH aqueous solution, and the voltage varied between 0-0.5V. The results are shown in Figure 7 As shown. When the voltage changes cyclically in the range of 0-0.5V, the composite material in Example 3 and the graded nanoporous copper in the comparative example can both achieve a length change between +0.02% and -0.07%, and the driving amplitude is 0.09%. It can be seen that the filling of polymers in the macropores does not lose the driving performance of nanoporous copper. At the same time, the improvement of plasticity is conducive to the application of nanoporous structures in the driving field.
Claims
1. A method for preparing a polymer / nanoporous copper composite material, characterized in that: The method comprises the following steps: (1) preparing a Mn-Cu binary alloy, or preparing copper and manganese and smelting them to prepare a Mn-Cu binary alloy; (2) performing homogenization annealing heat treatment on the Mn-Cu alloy to obtain a γ single-phase alloy, and rolling the alloy with a rolling reduction of 50% to 99% (preferably 60 to 98%, more preferably 80 to 95%); (3) subjecting the γ single-phase alloy to a recrystallization annealing heat treatment at a temperature of 700-900° C. (preferably 700-750° C., more preferably 720-750° C.) for a heat treatment time of 2-60 min (preferably 10-40 min, more preferably 20-30 min); (4) subjecting the γ single-phase alloy after recrystallization annealing to aging heat treatment to precipitate the α phase to obtain an α / γ dual-phase alloy; (5) placing the α / γ dual-phase structured Mn-Cu alloy in a weakly acidic aqueous solution for selective phase corrosion, wherein the α phase is completely corroded to form macropores, and the γ phase is retained to form porous γ-Mn(Cu); (6) using a vacuum impregnation method to immerse a liquid polymer material into the porous γ-Mn(Cu), and after the polymer material is solidified, a polymer / γ-Mn(Cu) dual-phase composite material is formed; (7) placing the prepared polymer / γ-Mn (Cu) dual-phase composite material in an acidic aqueous solution for electrochemical corrosion or free chemical corrosion until the Mn element content in the metal phase is less than or equal to 2 at.%, thereby forming nanoscale pores.
2. The preparation method according to claim 1, characterized in that: In step (1), the Mn content in the Mn-Cu binary alloy is in the range of 70%-90% (atomic percentage), preferably 80%-85%.
3. The preparation method according to claim 1, characterized in that: In step (2), the alloy is cooled to room temperature after heat treatment; the heat treatment temperature is 700-900°C (preferably 800-900°C, more preferably 830-880°C), the heat treatment time is 1-100h (preferably 10-50h), the cooling method is water cooling, and a γ single-phase alloy is obtained, and rolling is performed, the rolling passes are 5-50 times (preferably 10-20 times), and a plate-like material with a thickness of 0.1mm-10mm (preferably 0.5-5mm, more preferably 1-2mm) is formed after rolling.
4. The preparation method according to claim 1, characterized in that: In step (3), the γ single-phase alloy is subjected to recrystallization annealing, and then cooled to room temperature by water cooling.
5. The preparation method according to claim 1, characterized in that: In step (4), the γ single-phase alloy after recrystallization annealing is subjected to aging heat treatment to form an α / γ dual-phase structure, the aging heat treatment temperature range is 500-750°C (preferably 650-700°C), and the heat treatment time is 0.5-100h (preferably 1-20h, more preferably 3-8h); after the heat treatment, it is cooled to room temperature by water cooling.
6. The preparation method according to claim 1 or 5, characterized in that: In step (4), the γ single-phase alloy after recrystallization annealing is subjected to aging heat treatment to form an α / γ dual-phase structure, wherein the Mn content in the α phase is 98%-100% (atomic percentage), and the Mn content in the γ phase is 40%-70% (atomic percentage) (preferably 50-60%).
7. The preparation method according to claim 1, characterized in that: In step (5), during the selective phase corrosion process, the α phase is completely corroded, the γ phase is completely retained or only less than or equal to 20% of the Mn element is lost in the γ phase; the Mn-Cu alloy with an α / γ dual-phase structure is placed in a weakly acidic aqueous solution of one or more of acetic acid, ascorbic acid, ammonium sulfate, ammonium chloride, etc., with a volume of more than 100 times the volume of the alloy, and the solution concentration is 0.001-1 mol / L (preferably 0.1-0.2 mol / L), and selective phase corrosion is carried out at a corrosion temperature of 10-50° C. and a corrosion time of 1-200 h (preferably 5-24 h).
8. The preparation method according to claim 1, characterized in that: In step (6), the liquid polymer material used for impregnation is in liquid state before solidification and in solid state after solidification; The liquid polymer material is a uniform mixture of one or more of phenolic resin, epoxy resin, polycarbonate, polytetrafluoroethylene, etc. and a curing agent; The vacuum degree of the impregnation process is 0.01-100Pa, the impregnation temperature is 10-50°C, the impregnation time is 0.5-2h, the curing temperature is 10-380°C, and the curing time is 1-24h.
9. The method for preparing the polymer / nanoporous copper composite material according to claim 1, characterized in that: In step (7), the prepared polymer material / γ-Mn (Cu) dual-phase composite material is placed in an acidic aqueous solution of one or more of hydrochloric acid, sulfuric acid, phosphoric acid, oxalic acid, etc. with a sufficient concentration of 0.001-5 mol / L (preferably 0.01-0.1 mol / L), and free chemical corrosion or electrochemical corrosion dealloying (removal of Mn) is carried out until the Mn element content in the metal phase is less than or equal to 2 at.%; The free chemical corrosion temperature is 0℃-80℃, the electrochemical corrosion temperature is 0℃-80℃, and the electrochemical corrosion applied potential is -1V to +0.3V (standard electrode potential).
10. A polymer / nanoporous copper composite material prepared by the preparation method according to any one of claims 1 to 9, characterized in that: The width of the polymer phase is in the range of 0.5-10 μm, and the diameter of the small pores in the nanoporous Cu phase is in the range of 20-100 nm.
Citation Information
Patent Citations
Method for preparing multilayer-structured metal / nanoparticle composite material prepared by accumulation pack rolling and heat treatment
CN106583451A
Graded nano-porous copper and preparation method thereof
CN116770106A
Process for preparing metallic porous body, electrode substrate for battery and process for preparing the same
US5640669A
Porous materials and method for producing
WO1997031738A1